Read, Reason, Write: An Argument Text and Reader - Dorothy U. Seyler (McGraw Hill Higher Education, 2006)
Now in its 8th edition, this book equips students with all the skill they need to read and write arguments effectively, for the classroom and beyond. This comprehensive text presents clear instruction in critical reading, argument, research techniques, and visual rhetoric, along with a newly revised collection of current, incisive readings.